2016
DOI: 10.2147/ott.s119027
|View full text |Cite
|
Sign up to set email alerts
|

Different levels of serum microRNAs in prostate cancer and benign prostatic hyperplasia: evaluation of potential diagnostic and prognostic role

Abstract: IntroductionDiagnosis of prostate cancer (PCa) is based on prostate biopsy that is performed when prostate specific antigen (PSA) is persistently altered over time and/or abnormal digital rectal examination is found. Serum PSA levels increase in both PCa and benign prostatic hyperplasia, leading to an increased number of unnecessary biopsies. There is an urgent need to unravel PCa-specific molecular signatures.Patients and methodsThis study aimed at characterizing a panel of circulating micro RNAs (miRNAs) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 63 publications
3
98
0
Order By: Relevance
“…Many of them were identified by high‐throughput technologies and subsequently validated by standard PCR‐based methods; however, limited overlap has been observed among these findings. According to recently published studies, the most promising molecules for diagnosis and prognosis of PCa are miR‐1, miR‐18b‐5p, miR‐21, miR‐106b, miRNA‐141, miRNA‐145, miR‐182‐5p, miR‐200b‐3p, miRNA‐205, miRNA‐221, and miR‐375 . In the present study, only four miRNAs appeared to differentiate between non‐malignant and malignant prostate pathology, and there were only 17 in common among the 110 miRNAs reported here and 69 miRNAs reported by one of the largest and most comprehensive miRNA expression profiling studies of PCa to date .…”
Section: Discussionsupporting
confidence: 45%
“…Many of them were identified by high‐throughput technologies and subsequently validated by standard PCR‐based methods; however, limited overlap has been observed among these findings. According to recently published studies, the most promising molecules for diagnosis and prognosis of PCa are miR‐1, miR‐18b‐5p, miR‐21, miR‐106b, miRNA‐141, miRNA‐145, miR‐182‐5p, miR‐200b‐3p, miRNA‐205, miRNA‐221, and miR‐375 . In the present study, only four miRNAs appeared to differentiate between non‐malignant and malignant prostate pathology, and there were only 17 in common among the 110 miRNAs reported here and 69 miRNAs reported by one of the largest and most comprehensive miRNA expression profiling studies of PCa to date .…”
Section: Discussionsupporting
confidence: 45%
“…Typically Let‐7c, let‐7e, let‐7i, miR‐26a‐5p, miR‐26b‐5p, miR‐18b‐5p, and miR‐25‐3p are confirmed miRNAs as discriminative tools (Cochetti et al, ).…”
Section: Mirnas As Distinctive Markersmentioning
confidence: 99%
“…Ambs et al (7) studied the differences in miRNA and mRNA in 60 cases of prostate cancer and normal prostate tissue and revealed that miRNA is associated with the development of prostate cancer, and miRNA controls tumor growth by regulating the expression of tumor-associated genes to promote prostate cancer occurrence and development. Chen et al (8) and other comparative studies (9,10) of the expression of miRNA in the plasma of patients with prostate cancer and benign prostatic hyperplasia revealed that the expression of miR-622 and miR-1285 significantly increased, while the expression of let-7e, Let-7c and miR-30c significantly decreased. Therefore, the present study hypothesized that the differential expression of the 5 miRNAs in the plasma may be used as a biochemical marker and, combined with the prostate-specific antigen test, can be used in the diagnosis of prostate cancer.…”
Section: Introductionmentioning
confidence: 96%